1999
DOI: 10.1002/j.2161-0045.1999.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Search Techniques as Employment Channels: Differential Effects on the Initial Employment Success of College Graduates

Abstract: A conceptual framework suggests that employers will favor applicants from specific employment channels (job search techniques) depending on the qualifications sought. Logistic regression was used to analyze the responses of 1012 baccalaureate graduates to a survey 1 month after graduation. The results support the proposition t h a t alternative search techniques have differential effects depending on the qualifications offered. All search techniques except 1 revealed interaction effects, favoring or limiting g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…Although most literature indicated that the most effective job search method for white-collar workers is informal contact through networking, the present study showed that the formal approach through the journal of employment counseling ~eptember2001 Volume 38 use of r6sum6s and want ads seemed to be the most common job search method for college graduates. This finding extended the findings of previous studies (Ports, 1993;Sagen et al, 1999, Young, 1974) that more formal methods are most effective for college graduates and professional level employment. In many markets for professionals, the normal hiring procedure is to invite written applications for job openings advertised in newspapers, journals and periodicals, or in the universities through job placement offices.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although most literature indicated that the most effective job search method for white-collar workers is informal contact through networking, the present study showed that the formal approach through the journal of employment counseling ~eptember2001 Volume 38 use of r6sum6s and want ads seemed to be the most common job search method for college graduates. This finding extended the findings of previous studies (Ports, 1993;Sagen et al, 1999, Young, 1974) that more formal methods are most effective for college graduates and professional level employment. In many markets for professionals, the normal hiring procedure is to invite written applications for job openings advertised in newspapers, journals and periodicals, or in the universities through job placement offices.…”
Section: Discussionsupporting
confidence: 88%
“…The second is the hidden job information market, where positions are transmitted through informal contacts made by faculty, friends, and relatives and through direct application to employers of interest (Allen & Keaveny, 1980; Bowman, 1987). Various studies have been conducted comparing the use of the two types of information sources (e.g., Allen & Keaveny, 1980; Eby & Buch, 199% Sagen, Dallam, & Laverty, 1999, Silliker, 1993; also see review by Schwab, Rynes, & Aldag, 1987). Their results generally indicated that networking or the use of informal job information sources was the most common method to find a new position.…”
mentioning
confidence: 99%
“…A substantial proportion of individuals find their jobs due to the help of their personal networks. This result replicates that of studies conducted in the United States (Young, 1974;Sagen et al, 1999).…”
supporting
confidence: 80%
“…According to the participants, one of the best ways to get an industry job was through an internship. This finding is interesting in light of existing research on typical nonindustry‐specific job search methods (e.g., Mau & Kopischke, 2001; Sagen, Dallam, & Laverty, 1999), which does not report internships as a commonly used strategy to secure postgraduation employment. It was apparent that internships were helpful in the job search as experienced by the textile and apparel graduates in this study.…”
Section: Discussionmentioning
confidence: 80%